CD45RA Distinguishes CD4+CD25+CD127−/low TSDR Demethylated Regulatory T Cell Subpopulations With Differential Stability and Susceptibility to Tacrolimus-Mediated Inhibition of Suppression. Issue 2 (February 2017) - Arroyo Hornero, Rebeca; Betts, Gareth J.; Sawitzki, Birgit; Vogt, Katrin; Harden, Paul N.; Wood, Kathryn J.
Abstract : Background: Adoptive transfer of forkhead box protein (FOX)3 + regulatory T (Treg) cells offers a promising strategy to reduce damage to an allograft by the recipient's immune system. Identification of cell surface markers sufficient to purify Treg cells expanded ex vivo to remove cellular contaminants requires optimization. Furthermore, the expanded Treg must be able to survive, expand, and suppress in allograft recipients exposed to immunosuppressants, such as tacrolimus (TAC). Reduced CD127 expression enhances identification of Treg in the human CD4 + CD25 + population. CD45RA expression identifies naive CD4 + CD25 + Treg with an enhanced stability of Treg phenotype. Methods: We combine an analysis of CD45RA, CD25, and CD127 expression to identify subpopulations of CD4 + CD127 −/lo CD25 + cells. Regulatory T cells were sorted according to expression of CD25 and CD45RA and expanded in the presence of a physiological relevant concentration of TAC. Regulatory T cell–specific demethylation region (TSDR) demethylation, FOXP3 expression, and suppression were analyzed. Results: CD4 + CD127 −/lo CD25 + CD45RA + Treg cells had a stable TSDR demethylated FOXP3 + phenotype after expansion whereas CD4 + CD127 lo/− CD25 + CD45RA − Treg cell lost the TSDR demethylated phenotype. CD45RA − Treg had a greater capacity to suppress after expansion with TAC. Conclusions: Although CD45RA − Treg retained a greater suppressive capacity when expanded with TAC, the marked loss of the TSDR demethylated status highlights the potential for loss of stability of these cells in transplant recipients treated with TAC based immunosuppression. We show that a population of CD4 + CD127 −/lo CD45RA + Regulatory T cell may offer the best compromise between susceptibility to loss of suppression when exposed to TAC and maintenance of a TSDR demethylated phenotype following in vitro expansion. Abstract : Following in vitro expansion with tacrolimus, CD4+CD127-/loCD25+CD45RA- Treg had a greater suppressive capacity vs the CD45RA+ counterpart Treg. Nevertheless, CD45RA+ Treg had a more stable TSDR demethylated FOXP3+ phenotype vs the CD45RA- Treg counterpart. CD4+CD127-/loCD25+CD45RA+ Treg offer the best compromise following expansion. Supplemental digital content is available in the text.